ECONOMETRIC ASSESSMENT OF THE EFFICIENCY OF USING INVESTMENTS IN KHORAZM REGION (Marketing Journal, 2025)
This study examines the issues of improving the investment climate and increasing the efficiency of attracting investments in the Khorezm region of the Republic of Uzbekistan. Economic analyses were carried out based on scientific abstraction, analysis, sy nthesis, induction, and deduction methods. Currently, numerous agreements are being signed to encourage and protect foreign investments in the country. The main tasks and proposals of state policy for improving the investment environment are presented.
Keywords: investment; economic analysis; foreign investments; investment climate; incentives; efficiency; economic development